The computer, information and communication technology, and communication skills of Thai Rajabhat University students - Siphai, Sunan; Siphai, Jirattikorn; Saengloetuthai, Jittirat; Sakulku, Jaruwan (Institute of Advanced Engineering and Science, 2025)
The lack of comprehensive data on computer, information and communication technology (ICT), and communication skills among Thai Rajabhat University students poses a challenge in developing effective educational strategies that enhance student employability and future readiness. To address this gap, this study aimed to assess these skills and analyze the skill profiles of students from Rajabhat Universities across Thailand. A total of 1,165 students were selected through multi-stage sampling, and their skills were measured using a researcher-developed 5-point Likert scale questionnaire. The results showed high levels of self-reported skills, with communication skills being the highest (mean=3.84, SD=0.669), followed by ICT (mean=3.81, SD=0.676) and computer skills (mean=3.65, SD=0.628). Latent profile analysis (LPA) identified four potential models with 2, 3, 4, and 5 groups, with the four-group model offering the best fit (likelihood=-1887.336, Akaike information criterion (AIC)=3810.673, Bayesian information criterion (BIC)=3901.762, Akaike’s Bayesian information criterion (ABIC)=3844.587, entropy=0.940). These findings provided critical insights for curriculum development and tailored interventions, supporting universities in meeting diverse student needs and improving educational outcomes.